Utilization of young coconut fiber activated carbon with pre-carbonization variations as a supercapacitor electrode - Winda Nofriyanti; Awitdrus Awitdrus (Universitas Riau, 2024)
A supercapacitor is an electrochemical device that integrates power supply and charge storage capabilities. The primary constituents of a supercapacitor consist of electrodes, separator, electrolyte, and current collector. This work focuses on the production of carbon electrodes using coconut fibre biomass waste. The carbonisation process is carried out at three different temperatures: 200ºC, 225ºC, and 250ºC. The resulting samples are labelled as SC-200, SC-225, and SC-250, respectively. The production of Carbon electrodes involves multiple procedures, including pre-carbonization, chemical activation using a ZnCl2 activator at a concentration of 0.5 M, followed by carbonisation using N2 gas at a temperature of 600ºC, and physical activation using CO2 gas at a temperature of 750ºC. The mass reduces by 23.01%, 27%, and 36.51% following pre-carbonization. The sample with the greatest density value is SC-225, which has a mass loss percentage of 41.66%. The results of cyclic voltammetry indicate that the SC-225 supercapacitor cell has the maximum capacitance value of 199.82 F/g. To summarise, the SC-225 temperature can function as an activated carbon electrode that enhances the performance of the supercapacitor electrode.